Assessing of a Radiation Therapy Sessionʼs Duration at the Stage of Pre-Radiation Preparation - M. N. Piatkevich; E. V. Titovich (Приборы и методы измерений, 2022)
The treatment planning process includes a review of the radiation treatment plan which leads to a decision on the patientʼs treatment technique. The scope of this study was to create a mathematical model for calculating of a radiation therapy session duration during the pre-radiation planning stage.For dosimetric planning of radiation treatment the authors provided a formula and an algorithm for determining of a patientʼs irradiation session duration. Radiation therapy session parameters such as radiation technique, number of monitor units, characteristics of radiotherapy equipment, number of radiation fields, radiation field parameters (angles of rotation of the radiotherapy coach, collimator, gantry), presence / absence of dose-modulating devices, dose rate, and duration of patient position verification procedures have all been taken into account during the development of software. The developed application explains how to define typical timing characteristics for various items as well as how to select a template from a built-in drop-down menu. If the dosimetric plan does not match for one of the templates, the program provides a space for defining of all parameters manually.The anticipated deviations of the true indicators from the expected indicators of the duration of the radiation therapy session were assessed. A total of 300 cases have been completely measured, with 100 cases studied for each irradiation technique (IMRT, VMAT, 3D). The maximum detection confidence value for the 3DCRT irradiation technique is 2.3 %, while the deviation for the IMRT and VMAT irradiation techniques is less than 1 %. The magnitude and degree of the deviation of the measured value from the expected one for a variety of characteristics and features have been revealed to depend on the actions of the personnel.The program developed allows medical physicists to analyze the timing parameters of the specified dosimetric planning methodologies directly on the treatment planning workstation. Evaluation of the duration of a radiation therapy session during the treatment planning stage, selection of various radiation treatment modalities, and consideration of the characteristics of the radiation session in each clinical case are available for analysis and further justified action.